Shake table tests of structures subject to pounding - Crozet, Vincent; Politopoulos, Ioannis; Chaudat, Thierry (Earthquake engineering & structural dynamics, 2019)
Summary Pounding between adjacent structures during earthquakes may significantly modify their response in terms of forces and displacements. In addition, it has a considerable influence on acceleration and thus on floor response spectra. Therefore, pounding may be unfavorable to the response of equipment. Despite extensive research in this field, the effects of pounding on structures are difficult to quantify accurately. This article presents results of shake table tests carried out on two representative scale adjacent structures subject to pounding. Besides investigating the effects of the gap between structures and the excitation signal, this study examines also the effect of tying the two structures together by means of rigid links to suppress pounding. The results of the experimental campaign are then compared with those of numerical simulations. Analyses and experimental results show good agreement regarding both impact forces and interstorey drifts.